2016
DOI: 10.3389/fimmu.2016.00401
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Immune Cells in Tertiary Lymphoid Organ Development: It Is All Starting to Come Together

Abstract: Tertiary lymphoid organs (TLOs) are frequently observed in tissues affected by non-resolving inflammation as a result of infection, autoimmunity, cancer, and allograft rejection. These highly ordered structures resemble the cellular composition of lymphoid follicles typically associated with the spleen and lymph node compartments. Although TLOs within tissues show varying degrees of organization, they frequently display evidence of segregated T and B cell zones, follicular dendritic cell networks, a supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
138
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 123 publications
(140 citation statements)
references
References 118 publications
2
138
0
Order By: Relevance
“…Homeostatic chemokines play a central role in the development of secondary lymphoid organs and TLSs,4, 12 and our earlier data revealed transcripts for Cxcl13 , Ccl19 , Ccl21 and Cxcl12 in laser microdissected TLSs from 6‐month‐old gp130 F/F mice with well‐established gastric tumours (see Fig. 1 h ).…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Homeostatic chemokines play a central role in the development of secondary lymphoid organs and TLSs,4, 12 and our earlier data revealed transcripts for Cxcl13 , Ccl19 , Ccl21 and Cxcl12 in laser microdissected TLSs from 6‐month‐old gp130 F/F mice with well‐established gastric tumours (see Fig. 1 h ).…”
Section: Resultsmentioning
confidence: 61%
“…1 d ). TLSs also contained podoplanin (Pdpn; also called gp38) expressing cells, marking the presence of stromal cells required for lymphoid organ development, and the support of lymphocyte migration and antigen presentation4, 35 (Fig. 1 d ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Despite the well-characterized role of infiltrating B cells and TLOs, the role of Tfh in human lung cancers remains understudied. 7 Infection models have revealed that circulating Tfh function differently from those in lymphoid tissue and correlate with opposing outcomes. 8 In human breast cancers and mouse models of colorectal cancer, increased Tfh correlates with increased survival.…”
Section: Introductionmentioning
confidence: 99%